Perceived Psychological Feelings Make Important Contributions to the Symptoms of Common Mental Disorders of Medical Staff During the COVID-19 - Han, Bing; Ma, Chao; Liu, Zhaorui; Jiang, Rongmeng; Zhang, Tingting; Wang, Ying; Chen, Hongguang; Wen, Jing; Huang, Yueqin (Frontiers in Psychiatry, 2022)
Objective Lack of information about mental health status among medical staff during the epidemic of COVID-19 in China is one of the major barriers to psychological interventions. This paper aims to evaluate the contributions of perceived psychological feelings to the symptoms of common mental disorders among medical staff during the epidemic of COVID-19 in China. Method A large sample of medical staff based on a non-probability sampling design was collected from February 17 to 24, 2020. The symptoms of common mental disorders were screened based on self-reported instruments to evaluate psychological distress, anxious symptoms, and depressive symptoms during the past week. Perceived psychological feelings were based on self-report. Logistic regressions and elastic net regularizations were used to evaluate the independent effect of the psychological feelings controlled by hospitals and participants characteristics. Results Totally 4,677 medical staff completed the survey. The prevalence of psychological distress, anxious symptoms, and depressive symptoms were 15.9% (95% CI 14.8–16.9), 16.0% (95% CI 15.0–17.1), and 34.6% (95% CI 33.2–35.9). Feelings of having adequate personal protective equipment, receiving enough emotional supports from both family members and colleagues were significantly associated with fewer symptoms of common mental disorders, while the feelings of overloaded work and insufficient rest times contributed to more psychological problems. Conclusions Psychological feelings make important contributions to the symptoms of common mental disorders of medical staff during the epidemic of COVID-19. Strategies of psychological aids or interventions could be developed based on these feelings.